Comparative analysis of operation time and intraoperative fluoroscopy time in intramedullary and extramedullary fixation of trochanteric fractures - Mitković, Milan M.; Milenković, Saša; Micić, Ivan; Stojiljković, Predrag; Kostić, Igor; Mitković, Milorad B. (Vojnosanitetski pregled, 2022)
Background/Aim. Cephalomedullary and extramedullary methods are used for the internal fixation of trochanteric fractures. The usage of the third generation Gamma Nail (GN) is a gold standard in this kind of treatments. Self-dynamisable Internal Fixator (SIF) is an extramedullary implant for trochanteric fractures’ treatment. The aim of this study was to compare these two methods regarding operation time and intraoperative fluoroscopy time. Methods. A total of 89 patients with a surgical treatment of a trochanteric fracture were included in this study. There were two groups of patients – GN group (43 patients) and SIF group (46 patients). Results. Average operation times were 67.5 min (GN group) and 56.0 min (SIF group). Average intraoperative fluoroscopy times were 84.8 s (GN group) and 36.7 s (SIF group). The difference between the groups was statistically significant for both of the given parameters (p
Keywords: external fixators; femoral fractures; fluoroscopy; internal fixators; intraoperative period; orthopedic procedures